2003
DOI: 10.1113/jphysiol.2003.050369
|View full text |Cite
|
Sign up to set email alerts
|

Cold Exposure Induces Tissue‐Specific Modulation of the Insulin‐Signalling Pathway in Rattus Norvegicus

Abstract: Cold exposure provides a reproducible model of improved glucose turnover accompanied by reduced steady state and glucose-induced insulin levels. In the present report we performed immunoprecipitation and immunoblot studies to evaluate the initial and intermediate steps of the insulin-signalling pathway in white and brown adipose tissues, liver and skeletal muscle of rats exposed to cold. Basal and glucose-induced insulin secretion were significantly impaired, while glucose clearance rates during a glucose tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
74
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 51 publications
10
74
2
4
Order By: Relevance
“…Studies of insulin production and action and of glucose uptake in homeothermic animals exposed to cold revealed that, in this particular physiological condition, glucose is efficiently mobilized, despite low blood insulin levels and an apparent tissue-specific resistance to insulin's action (7,11,41,45). Therefore, it became clear that mechanisms that act independently of insulin signaling through the IR-IR substrates (IRSs)-Akt pathway play an important role in the control of glucose disposal in coldexposed animals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies of insulin production and action and of glucose uptake in homeothermic animals exposed to cold revealed that, in this particular physiological condition, glucose is efficiently mobilized, despite low blood insulin levels and an apparent tissue-specific resistance to insulin's action (7,11,41,45). Therefore, it became clear that mechanisms that act independently of insulin signaling through the IR-IR substrates (IRSs)-Akt pathway play an important role in the control of glucose disposal in coldexposed animals.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue uptake of 2-DG was measured in vivo according to a method described previously (44) with minor modifications (11). The rats were anesthetized and then injected through the portal vein with 6.0 Ci of 2-DG and [ 14 C]sucrose in the presence or absence of 0.1 U of insulin in 0.4 ml of isotonic phosphate buffer (pH 7.4) with 0.1% defatted BSA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations